2011
DOI: 10.1093/bja/aer119
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide predicts long-term survival after major non-cardiac surgery

Abstract: BNP is an independent predictor of long-term survival after major non-cardiac surgery. A simple preoperative blood test can provide predictive information on future risk of death, and potentially has a role in preoperative risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In total, 24 of the 28 studies 29,[34][35][36][37][38][40][41][42][43][46][47][48][49][50][51][52][53][55][56][57][58][59][60] were prospective observational cohort studies. Of the remaining four studies: …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 24 of the 28 studies 29,[34][35][36][37][38][40][41][42][43][46][47][48][49][50][51][52][53][55][56][57][58][59][60] were prospective observational cohort studies. Of the remaining four studies: …”
Section: Methodsmentioning
confidence: 99%
“…Of the remaining studies, three reported exclusively on patients undergoing emergency surgery, 38,45,48 and one documented both elective and emergency surgeries that were classified as being high risk. 46 Certain studies investigated outcomes in a specific surgical discipline, including thoracic surgery (4), 36,50,51,54 vascular (7), 29,40,42,44,55,57,59 orthopaedic (5), 45,[47][48][49]60 major abdominal (1), 56 oesophagectomy (1), 41 while the rest documented outcomes following a variety of surgeries performed (10), 34,35,[37][38][39]43,46,52,53,58 including a mix of general, head and neck, gynaecological, orthopaedic, vascular, urological, neurosurgery and thoracic surgery.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies measuring BNPs in patients undergoing noncardiac surgery have investigated the role in the perioperative period for risk prediction or associations with adverse postoperative myocardial events [35][36][37][38][39][40][41][42][43][44], prolonged hospital stay [45] and mortality [24,[46][47] (see Table 4). Most of the studies evaluating BNPs had levels drawn within 2 weeks prior to the day of surgery, typically at one time-point, however recent studies have incorporated perioperative BNP levels (levels drawn preoperatively and up to 5 days following surgery) [36,38,43,[45][46].…”
Section: Brain Natriuretic Peptides As a Marker Of Cardiovascular Rismentioning
confidence: 99%